Origins of Electron-Transfer Regime in Persulfate-Based Nonradical Oxidation Processes - Ren, Wei; Cheng, Cheng; Shao, Penghui; Luo, Xubiao; Zhang, Hui; Wang, Shaobin; Duan, Xiaoguang (Environmental science & technology, 2022)
Persulfate-based nonradical oxidation processes (PS-NOPs) are appealing in wastewater purification due to their high efficiency and selectivity for removing trace organic contaminants in complicated water matrices. In this review, we showcased the recent progresses of state-of-the-art strategies in the nonradical electron-transfer regimes in PS-NOPs, including design of metal and metal-free heterogeneous catalysts, in situ/operando characterization/analytical techniques, and insights into the origins of electron-transfer mechanisms. In a typical electron-transfer process (ETP), persulfate is activated by a catalyst to form surface activated complexes, which directly or indirectly interact with target pollutants to finalize the oxidation. We discussed different analytical techniques on the fundamentals and tactics for accurate analysis of ETP. Moreover, we demonstrated the challenges and proposed future research strategies for ETP-based systems, such as computation-enabled molecular-level investigations, rational design of catalysts, and real-scenario applications in the complicated water environment. Overall, this review dedicates to sharpening the understanding of ETP in PS-NOPs and presenting promising applications in remediation technology and green chemistry.